Analisis Semiotika Komunikasi Non-Verbal dalam Pertunjukan Teater Fisik Kontemporer: Telaah Pustaka Gerakan dan Makna - Inosensius Enryco Mokos; Moch Gigin Ginanjar; Denhaz Nurul Hakim; Aldi Nurhadiat Iskandar (LP2M ISBI Bandung, 2026)
This article analyzes in depth how nonverbal communication elements function as a system of signs and symbols to convey meaning, emotion, and narrative in contemporary physical theater performances. By highlighting gestures, mimics, body postures, proxemics (the use of personal space), and the use of stage space, this research explores the crucial role of the body in creating a rich artistic language, often without or with minimal verbal dialogue. Through a qualitative literature review informed by Ferdinand de Saussure's semiotic approach, this article examines Saussure's theoretical framework, particularly the concepts of the signifier and the signified, the arbitrary and conventional nature of signs, and their application in the critique of physical theater performances. This methodology allows for the dismantling of the complex signifying system in the performance, where every movement and expression is part of a larger system of meaning. The results show that non-verbal communication in physical theater is a complex and integrated semiotic system that allows the audience to interpret layers of meaning through the interaction of visual and spatial signs, grounded in the dynamic relationship between signifier and signified. This research contributes to a richer understanding of the expressive power of physical theater and the potential of Saussure's semiotics in analyzing the depth of non-verbal communication in contemporary performance art.